TEKNIK BUDIDAYA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq) BELUM MENGHASILKAN DI LAHAN PASANG SURUT YANG DILAKUKAN PETANI DI KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Hartono, Budi; Manurung, Gulat ME; ', Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Oil palm(Elaeis guineensisJacq) comefromNigeria, West Africa. This plant is adominantcropplantationinIndonesia, especiallyin Riau. Common problems of palm plantationsare include in low productivityandquality of production. One of thecauses oflow productivity due totheappliedproductiontechnologyis stillrelativelymodest, rangingfromnurserytoharvest. Oil palm plantations in Bangko Pusako district is a large area of tidal lands especially Bangko Kanan village and Bangko Kiri village that are managed by the Department of Horticulture and by farmers. This study aims to determine the technical implementation of oil palm (Elaeis guennensis Jacq) cultivation in tidal lands are held by non-government in Bangko Pusako, Rokan Hilir. This research was carried in August 2013 to October 2013 in Bangko Pusako district with three typeof tidal lands. This study used a survey method and the number of samples was 5% of the population. The sampling techniqueused wasPurposiveRandom Sampling. The results showed thatoil palmcultivationtechniqueswerecarried outbyfarmersin the District ofBangkoPusako, rangingfromseedlingstomaintenanceonly27,7% whofollow the suggestion/recommendations from RokanHilirDepartment of Horticulture. This is due to the sample farmers less understanding about the right oil palm cultivation techniques. The reason is most of the sample farmers follow the oil palm cultivation techniques were done by the previous farmers. Keyword : Oil Palm, Tidal Lands, Cultivation Techniques